2015
DOI: 10.1121/1.4935081
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-temporal modulation detection in children

Abstract: Children's performance on psychophysical tasks improves with age. The relationship of spectro-temporal modulation detection to age, particularly in children who are hard of hearing, is not well-established. In this study, children with normal hearing (N = 22) and with sensorineural hearing loss (N = 15) completed measures of spectro-temporal modulation detection. Measures of aided audibility were completed in the children who are hard of hearing. Pearson product-moment correlations were completed with listener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 8 publications
6
24
2
Order By: Relevance
“…Mature SRD thresholds were observed in school-age children regardless of hearing method. These results are consistent with previous work demonstrating adult-like SRD in both NH and CI children at the age ranges tested (Jung et al, 2012;Peter et al, 2014;Kirby et al, 2015). The finding that SMTF slopes were flatter in CI listeners than in NH listeners but mature in both groups of children supports the hypothesis that frequency resolution is limited by hearing method but mature at least by school-age.…”
Section: A Frequency Resolution and Srdsupporting
confidence: 92%
See 1 more Smart Citation
“…Mature SRD thresholds were observed in school-age children regardless of hearing method. These results are consistent with previous work demonstrating adult-like SRD in both NH and CI children at the age ranges tested (Jung et al, 2012;Peter et al, 2014;Kirby et al, 2015). The finding that SMTF slopes were flatter in CI listeners than in NH listeners but mature in both groups of children supports the hypothesis that frequency resolution is limited by hearing method but mature at least by school-age.…”
Section: A Frequency Resolution and Srdsupporting
confidence: 92%
“…Spectral resolution matures gradually in NH listeners (Blagosklonova et al, 1989;Peter et al, 2014;Rayes et al, 2014;Kirby et al, 2015). Previous research has shown that NH human infants can perceive changes in spectral patterns and shape (Trehub, 1973;Tsang and Trainor, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Taken with the limited literature on SRD in older children, this would place the age of maturation for SRD somewhere between 7-months-old and 8–11 years for NH listeners (Blagosklonova et al 1989, Allen and Wightman 1994, Jung et al 2012, Peter et al 2014). Recently, similar rates of spectral resolution maturation have been reported for tasks involving minimum-phase difference detection (Rayes et al 2014) as well as dynamic spectro-temporal phase detection (Rayes et al 2014, Kirby et al 2015). …”
Section: Discussionsupporting
confidence: 54%
“…Recently, a modified version of the traditional spectral ripple test, the Spectral-temporally Modulated Ripple Test (SMRT; Aronoff & Landsberger 2013) has been used in a number of studies (Vickers et al 2016; Holden et al 2016; Aronoff et al 2016b; Kirby et al 2015; Zhou 2017). The SMRT uses a spectral ripple with a ripple phase that drifts over time.…”
Section: Introductionmentioning
confidence: 99%